EFFECT OF PARTIAL REPLACEMENT OF SOME PLANT SOURCES IN QUALITY AND SENSORY CHARACTERISTICS OF PROCESSED OF GOOSE MEAT BURGER - & Al-Shamery, Zangana (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The aim of this experiment was to study the effect of replacing of some plant sources oat , wheat germ, rice and mushroom with percent 10% for each instead of goose meat on chemical composition , physical , microbial and sensory characteristics of process burger . The results showed significant increase (p<0.01)in moisture percent for replacing treatments and significant(P<0.05)in percent protein for replacing with wheat germ (T3) , while there was decreased in percent of fat and ash for replacing with mushroom(T5) compared with control(T1) in process burger . Significant increase (p<0.05) in value of pH and water holding capacity for T5 with significant decrease (p<0.05) in cooking loss percent , drip loss and shrinkage percentage for T4 , T5 compared with control (T1) . The result of microbial tests showed significant reduced (p<0.01)in arobic total bacterial count and coliform bacteria for T5 compared with other treatments . The Sensory evaluation data of flavour , juiciness , tenderness and overall were significant increase (P<0.05) when replacing some plant sources in this product. In conclusion the results revealed the possibility of replacing 10% of oat , germ wheat , rice and mushroom to goose meat burger which improved some chemical composition , physical , sensory evaluation of processed product without showing undesirable changes in quality of processed product .